Perancangan Aplikasi Dashboard Untuk Monitoring Penjualan Gas LPG Berbasis Web - Rusdiyanto, Rusdiyanto (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2019)
Currently PT. Rivet Jaya Lubuklinggau conducts the processing of LPG Gas sales data processing is still done with a manual system, the data processing process is still carried out with Microsoft Excel application tools to generate recapitulation (summary content or final summary report) of sales data such as the total sales amount. This study uses data collection methods by observing PT. Kelingi Jaya Lubuklinggau, interview with the head of PT. Kelingi Jaya Lubuklinggau and literature on books related to the author's title. The results of the research are the Dashboard Application for Monitoring the Sales of LPG Gas at PT. Kelingi Jaya Lubuklinggau, the application was built with the PHP programming language with MySQL as an application database and web-based application interfaces. It can be concluded that the application that has been built can do sales data collection and can display details of the overall sales data that will be used as a tool for PT. Kelingi Jaya Lubuklinggau to conduct monitoring.